2017
DOI: 10.1007/s12272-017-0898-x
|View full text |Cite
|
Sign up to set email alerts
|

The anti-HSV-1 effect of quercetin is dependent on the suppression of TLR-3 in Raw 264.7 cells

Abstract: Quercetin is a major component of the plant Glycyrrhiza uralensis, which is largely used as a traditional medicine in Asia. Quercetin has been reported to have several biological activities, which include anti-viral and anti-inflammatory effects. We explored the molecular mechanism linking anti-viral and anti-inflammatory activities using an in vitro herpes simplex virus-1 (HSV-1) infection model. Raw 264.7 cells were infected with HSV-1 in the presence or absence of different concentrations of quercetin and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 26 publications
1
36
0
3
Order By: Relevance
“…C10 and C11 reduced significantly the areas of formed viral plaques when compared to viral controls, and these results could be a consequence of the inhibition of viral release. Several studies have demonstrated the anti-herpes activity of natural products, some of which interfere with early steps [41,42,[56][57][58][59][60][61][62][63][64], while a few affect the last steps of HSV replication [65][66][67][68], as was demonstrated for C10 and C11. For this reason, both cardenolides could be used in combination with other natural products to ensure that different stages of HSV replication would be inhibited, for example with transresveratrol, for which significant anti-HSV activity has also been described [69].…”
Section: Discussionmentioning
confidence: 83%
“…C10 and C11 reduced significantly the areas of formed viral plaques when compared to viral controls, and these results could be a consequence of the inhibition of viral release. Several studies have demonstrated the anti-herpes activity of natural products, some of which interfere with early steps [41,42,[56][57][58][59][60][61][62][63][64], while a few affect the last steps of HSV replication [65][66][67][68], as was demonstrated for C10 and C11. For this reason, both cardenolides could be used in combination with other natural products to ensure that different stages of HSV replication would be inhibited, for example with transresveratrol, for which significant anti-HSV activity has also been described [69].…”
Section: Discussionmentioning
confidence: 83%
“…Some reports investigated that medicines can affect viruses replication by activating or suppressing TLR3 media apoptosis signaling [11,12], we investigated whether YASML can activate TLR3 to involve in the anti‐PRRSV replication for previous research shown that YASML seemed to induce the activation of apoptotic pathway (Figure 2a,b). So, we knocked down the expression of TLR3 by siRNA.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, 51 inhibited the HSV-1-induced nuclear factor (NF)-κB activation through blocking the nuclear translocation and DNA binding of NF-κB. The study of Lee et al [28] gave some insight into the effect of flavonoids, showing the ability of quercetin (19), a "prototype" of flavonoid, to inhibit the expressions of HSV proteins (gD, ICP0) and genes (ICP0, UL13, UL52), and specifically suppress the expression of TLR-3 and inhibit the transcription factors NF-κB and IRF3 [28]. The antiviral activity of halistanol derivatives (96 and 97) against HSV-1 is enabled by the inhibition of viral particles' attachment and penetration; the virucidal effect was also observed.…”
Section: Discussionmentioning
confidence: 99%